THE INFLUENCE OF THE TAX WAIVER PROGRAM AND THE QUALITY OF MOBILE SAMSAT SERVICES ON TAXPAYER COMPLIANCE IN PAYING MOTOR VEHICLE TAXES (Case Study at SAMSAT Pajajaran I Office, Bandung City) - Verawati Febriani Sasmita; Sa'adah Sa'adah (Jurnal Ekonomi, 2023)
This research is to determine the influence of the tax waiver program and the quality of mobile SAMSAT services on taxpayer compliance in payment of motor vehicle taxes at the SAMSAT Pajajaran I office in Bandung City. The tax waiver program and the quality of mobile SAMSAT are experimental variables in this study. Taxpayer compliance is the dependent variable in this study The population of this study are taxpayers registered at the SAMSAT Pajajaran office. The taxpayers registered at the Pajajaran SAMSAT office in 2022 were 550,542 taxpayers. This study using a sample with the Non-Probability Sampling method with Purposive Sampling technique with the several key of taxpayers registered at the SAMSAT Pajajaran office and taxpayers who use SAMSAT Mobile services. Primary data in this study were obtained from the answers to questionnaires distributed to 100 taxpayers at the SAMSAT Pajajaran and SAMSAT mobile offices. Secondary data used is data on the potential of motorized vehicles that will support this research. Multiple Linear Regression is used as a data analys method. The findings of the study the tax waiver program had a significant effect with a significant value of 0.015 <0.05 and the quality of mobile SAMSAT positive and significant impact with a significant value of 0.000 <0.05. Simultaneously, all variables affect taxpayer obedience in payment of motor vehicle tax at SAMSAT Pajajaran.